Reaktualisasi Maqasid Al-Shariah dalam Etika Ekonomi Islam di Era Digitalisasi Global - Sulistiyah Sulistiyah; Arifah Rohmatul Hidayah (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The rapid expansion of global digitalization has significantly transformed economic activities, enhancing efficiency while simultaneously generating ethical challenges such as data exploitation, consumer manipulation, and profit-oriented business practices that often neglect moral considerations. This study aims to examine the relevance of maqāṣid al-Shariah as an ethical and normative framework for guiding Islamic economic practices in the digital era toward justice, sustainability, and social welfare. Employing a qualitative library research method, this study analyzes contemporary and classical literature sourced from national and international academic publications related to Islamic economics, digital transformation, and maqāṣid-based ethics. The findings reveal that the core principles of maqāṣid al-Shariah including the protection of religion, life, intellect, wealth, and progeny provide a comprehensive ethical foundation for regulating digital economic activities across production, consumption, and public policy domains. These principles emphasize a balance between technological innovation and moral responsibility, ensuring transparency, fairness, data protection, and long-term societal well-being. This study contributes to the discourse on Islamic digital economics by positioning maqāṣid al-Shariah not merely as a normative concept but as a strategic ethical framework capable of addressing contemporary digital economic challenges in a holistic and sustainable manner.